2005
DOI: 10.1111/j.1467-6486.2005.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmentation of a Railway: A Study of Organizational Change

Abstract: This paper considers pathways of organizational change within British Rail (BR) during its long period of commercialization culminating in privatization. The Laughlin (1991) and Parker (1995a) frameworks are used to demonstrate how a new interpretative scheme supplanted the previous interpretative scheme within BR between the 1970s and privatization in the mid-1990s, leading to a fragmented organization. BR did not survive and privatization of Britain's railways remains controversial. The study demonstrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Within a corporation, metarules are likely to be focused on the maximisation of profit. Cultures, beliefs, values, and norms comprise a secondary level to an organisation's interpretive schemes (Tyrrall and Parker 2005). Organisational culture will not necessarily be integrated and homogeneous; Martin (1992) suggests that culture might differ from one organisational sub-unit to another, or be fragmented.…”
Section: What Is Water Management?mentioning
confidence: 99%
“…Within a corporation, metarules are likely to be focused on the maximisation of profit. Cultures, beliefs, values, and norms comprise a secondary level to an organisation's interpretive schemes (Tyrrall and Parker 2005). Organisational culture will not necessarily be integrated and homogeneous; Martin (1992) suggests that culture might differ from one organisational sub-unit to another, or be fragmented.…”
Section: What Is Water Management?mentioning
confidence: 99%
“…His subsequent research (1992) on changes of MAS following management buy-out showed that owner-managers use MAS in a selective manner to facilitate changes in organisational structures and in the attitudes of participants, and to improve efficiency and profitability. More recently, Tyrrall and Parker (2001) investigated the changes of accounting systems in British…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research on the differences of management control between the public and the private or privatised sector is scarce and often inclusive 5 (Boardman and Vining, 1988;Cragg and Dyck, 1999;Martin and Parker, 1997;Karatas, 1995;Jones, 1985;Tyrrall and Parker, 2001;Letza and Smallman, 2001). Very few studies have researched the changes in control, performance and accountability after privatisation in less developed and post-communist countries.…”
Section: Public Sector Reforms Privatisation and Developmentmentioning
confidence: 99%
“…In other words, they should "…bind the organization together and make it a coherent whole" (Laughlin, 1991, p. 213). According to Tyrrall and Parker (2005), however, the organizational change model given by Laughlin (1991) emphasizes more on the design archetypes of an organization. Since the adjusting and tailoring of design archetypes of an organization is a job that pertains purely to the senior management, Tyrrall and Parker (2005) argue that in most studies that resort to Laughlin's model the focus is on looking at the organizational change from the top management point of view rather than other staff levels.…”
Section: Organizational Transformationmentioning
confidence: 99%
“…A number of frameworks have been devised by organizational and other researchers for the analysis of organizational change (Tyrrall & Parker, 2005). The 'organizational change' dimension of the microfinance sector's paradigm shift could be best analysed by the Laughlin's (1991) organizational change theoretical conceptualization (see figure 1 below).…”
Section: Organizational Transformationmentioning
confidence: 99%